Small RNA binding-site multiplicity involved in translational regulation of a polycistronic mRNA - Rice, Jennifer B. (National Academy of Sciences, 2012)
In animal systems, mRNAs subject to posttranscriptional regulation by small RNAs (sRNAs) often possess multiple binding sites with imperfect complementarity to a given sRNA. In contrast, small RNA–mRNA interactions in bacteria and plants typically involve a single binding site. In a previous study, we demonstrated that the Escherichia coli sRNA SgrS base pairs with a site in the coding region of the first gene of a polycistronic message, manXYZ. This interaction was shown to be responsible for translational repression of manX and to contribute to destabilization of the manXYZ mRNA. In the current study, we report that translational repression of the manY and manZ genes by SgrS requires a second binding site located in the manX–manY intergenic region. Pairing at this site can repress translation of manY and manZ even when mRNA degradation is blocked. Base pairing between SgrS and the manX site does not affect translation of manY or manZ. Pairing at both sites is required for optimal SgrS-mediated degradation of the full-length manXYZ mRNA and for a particular stress phenotype. These results suggest that bacterial sRNAs may use target-site multiplicity to enhance the efficiency and stringency of regulation. Moreover, use of multiple binding sites may be particularly important for coordinating regulation of multiple genes encoded in operons.